2013
DOI: 10.1111/1346-8138.12071
|View full text |Cite
|
Sign up to set email alerts
|

Association of human leukocyte antigen class I antigens in Iranian patients with pemphigus vulgaris

Abstract: There are a limited number of reports indicating the role of human leukocyte antigen (HLA) class I alleles in pemphigus vulgaris. This study was designed to highlight the association of HLA class I alleles with pemphigus vulgaris in Iran. Fifty patients with pemphigus vulgaris, diagnosed based on clinical, histological and direct immunofluorescence findings were enrolled into this study. The control group consisted of 50 healthy, age- and sex-matched individuals. HLA typing of class I (A, B and C alleles) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
(52 reference statements)
4
16
0
3
Order By: Relevance
“…This is one of the most heterogenous cities in the world as a result of the great admixture between races, which promotes the unique characteristics of this population, favoring association studies, since the genes linked to the disease have a lower chance of being false positives because of their ancestry. 39 In the present study, we found that allele C*15 increased the risk of the disease threefold compared to the control group. 20 Another Iranian report identified that C*04, C*15, and C*16 conferred a risk of PV.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This is one of the most heterogenous cities in the world as a result of the great admixture between races, which promotes the unique characteristics of this population, favoring association studies, since the genes linked to the disease have a lower chance of being false positives because of their ancestry. 39 In the present study, we found that allele C*15 increased the risk of the disease threefold compared to the control group. 20 Another Iranian report identified that C*04, C*15, and C*16 conferred a risk of PV.…”
Section: Discussionsupporting
confidence: 50%
“…The question that remains is whether they are in the DR and/or in DRB1*08-DQA1*05:01-DQB1*03:01 38,39. The question that remains is whether they are in the DR and/or in DRB1*08-DQA1*05:01-DQB1*03:01 38,39.…”
mentioning
confidence: 99%
“…HLA-B*39:06 has been associated with a risk for Takayasu arteritis (Rodriguez-Reyna et al 1998; Salazar et al 2000; Vargas-Alarcon et al 2005). Preliminary studies have linked HLA-B*38:01 to multiple sclerosis and to protection from pemphigus vulgaris (Khankhanian et al 2015; Mortazavi et al 2013). …”
mentioning
confidence: 99%
“…The majority of genetic studies in patients with pemphigus show associations between PV and the major histocompatibility complex class II antigens, in particular, HLA-DR4 or HLA-DQ1. 9,10,38,39 Currently and with the advent of molecular sequencing, 2 HLA class II subtypes (DRB1*0402 and DQB1*0503) have been recognized as present in more than 95% of patients with PV. 11 Although the genetic predisposition is essential, it is not independently sufficient to initiate the autoimmune pathogenic mechanism leading to the diseases, as proven by the reports of pemphigus in one of two monozygotic twins and in only two of three siblings with identical predisposing haplotype.…”
Section: Etiology Genetic Backgroundmentioning
confidence: 99%
“…7,8 A genetic predisposition is known to be associated with human leukocyte antigens (HLA), in particular HLA-DR and HLA-DQ. [9][10][11] Although most cases occur spontaneously, in several cases, meticulous clinical history detects the presence of facilitating factors (inducing or triggered pemphigus). 4,[12][13][14] …”
mentioning
confidence: 99%